Samurai Japan [videorecording (DVD)] : a journey back in time (Lost treasures of the ancient world., 2000)
Explores the history and architecture of the ancient world and featuring graphics, computer animation, and location footage. Visits the great monuments, pagodas, and temples of Buddhist Japan and considers the Samurai warriors and their code of Bushido which stresses honor, self-discipline, bravery, and simple living, as it examines the traditional society of Japan and its emphasis on balance, order, and calm.